Implementation of Hygiene Sanitation Principles for Fried Snacks in Tamalanrea, Makassar City - Nursiah, Andi; Hermawan, Adi; Hardianti, Hardianti; Rahagia, Rasi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Snack foods are food and drinks that are processed by food producers at the point of sale and/or served as food ready for sale to the general public. Contaminated food can be caused by food sanitation hygiene that does not meet health requirements. Fried foods are one of the snack foods sold by street vendors. This research aims to determine the implementation of the health principles of sanitation for fried snack foods. The impact of consuming fried food continuously and excessively can have bad effects on the body, including obesity, increasing the risk of coronary heart disease and cancer due to carcinogenic substances produced from the frying process. The type of research used in this research is descriptive observational with a cross sectional approach. The population in this study were all fried food sellers in Tamalanrea, totaling 29 people. The sample in this research was all fried food sellers in Tamalanrea, namely 29 people, with a sampling technique using exhaustive sampling. The research results showed that of the 29 respondents, 27 respondents met the food selection requirements, 22 respondents met the food storage requirements, 26 respondents (89.7%) met the food processing requirements, 24 respondents (82.8%) met the food storage requirements, 27 respondents (93.1%) met the requirements for transporting food, and 23 respondents (79.3%) met the requirements for serving food.